Perlindungan Hukum Konsumen Akibat Pencabutan Izin Mendirikan Bangunan Apartemen (Studi Kasus di Kota Bandung) - Fauzan Aziman Alhamidy; isis Ikhwansyah; Zainal Muttaqin (Magister Kenotariatan, Universitas Jambi, 2020)
At present many people are interested in living in apartments. In its construction, an apartment requires a building permit (IMB). Apartment residents in this case referred to as consumers have rights and obligations towards the developer as a business actor and vice versa. In the legal relationship between businesspersons and consumers after the agreement, the consumer has the right to have an apartment unit that is suitable for use and is obliged to make payments to the developer. In the case of the city of Bandung there are still apartments that violate the IMB rules. This resulted in sanctions that would be given to developers by the City Government. This study aims to determine the responsibility of the developer to consumers if the IMB of the apartment is revoked and to find out how to legal protection against consumers if the IMB of the apartment is revoked by the Regional Government of the City. Based on the results of the study it can be stated that the developer's responsibility to the consumer is an absolute responsibility (strict liability) and responsibility responsibility based on the agreement (contractual liability). Absolute responsibility (strict liability) that is the business actor must be responsible for consumer losses without having to prove the presence or absence of error on the business actor. Efforts to protect consumers from consumers who are disadvantaged when the Permit for Building an Apartment is revoked by the Bandung City Government is done by taking a dispute resolution through the consumer dispute resolution agency because it is faster than the dispute resolution in a court that requires a long time, expensive court fees and the court is generally not responsive, Settlement of disputes at BPSK compared to through the courts, it is more flexible and can choose ways of resolving disputes in mediation, arbitration or conciliation and is more competent in resolving disputes in the field of consumer protection.Keywords: Government, Developers, Legal Protection of Consumers